Keputusan Berkunjung ke Desa Wisata Bojongkulur Gunung Putri Kabupaten Bogor yang Dipengaruhi oleh Fasilitas Tempat Wisata dan Kepuasan Pengunjung Dimoderasi oleh Loyalitas Pelanggan - Frimayasa, Agtovia; Nasution, Ibnu Haris; Purnama, Yanthy Herawaty (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to find out the decision to visit the Bojongkulur Gunung Putri tourist village, Bogor Regency which is influenced by tourist attraction facilities and visitor satisfaction is moderated by customer loyalty. This study uses a quantitative research method. In this study, the sampling technique used is probability sampling, with the sampling method used being simple random sampling. This study uses the Partial Least Squares (PLS) methodological analysis technique with smartPLS 3.0 software to assess the hypothesis. The results of the data analysis showed that (1) facilities had a positive and significant effect on the decision to visit, (2) visitor satisfaction with the decision to visit had a positive and significant effect, (3) visitor satisfaction with the decision to visit had a positive and significant effect, (4) visitor satisfaction with loyalty had a positive and significant effect, (5) loyalty to the decision to visit had a positive effect and significantly, (6) loyalty plays a role in mediating facilities against the decision to visit, and (7) loyalty plays a role in mediating visitor satisfaction with the decision to visit